Athlete support personnel and anti‐doping: Knowledge, attitudes, and ethical stance. Issue 5 (22nd May 2013) - Mazanov, J.; Backhouse, S.; Connor, J.; Hemphill, D.; Quirk, F.
<x xml:space="preserve">Abstract</x> Athlete support personnel (ASP) failing to meet responsibilities under the World Anti‐Doping Code risk sanction. It is unclear whether the poor knowledge of responsibilities seen in sports physicians and coaches applies to other ASP (e.g., administrators, chiropractors, family, nutritionists, physiotherapists, psychologists, and trainers). A purposive sample of Australian ASP (n = 292) responded to a survey on knowledge of anti‐doping rules (35 true/false questions), ethical beliefs and practice, and attitudes toward performance enhancement. Some ASP declined to participate, claiming doping was irrelevant to their practice. Physicians were most knowledgeable (30.8/35), with family and trainers the least (26.0/35). ASP reported that improvements were needed to support anti‐doping education (e.g., basis for anti‐doping) and practice (e.g., rules). ASP also had a slightly negative attitude toward performance enhancement. Linear regression showed that being a sports physician, providing support at the elite level, and 15 years of experience influenced knowledge. The results confirm gaps in knowledge, suggesting that stronger engagement with ASP anti‐doping education and practice is needed. Applying the principles of andragogy could help foster active engagement through emphasis on active inquiry, rather than passive reception of content. Future work on the context within which ASP experience anti‐doping is needed, exploring acquisition and translation of knowledge into practice.